Harnessing nature: Phytoextracts as sustainable remedies for fungal crop diseases - Nayeema jan; Mansoor Ahmad Malik; Nusrat Ahmad; Mohd Yaqub Bhat (The Microbe)
Since from dawn human civilization have relied on nature for solutions, finding natural products to be the most effective in maintaining development and the health of our environment. Fungal pathogens are a major contaminant in agroecosystems, causing around 70–80 % of microbial crop losses. To combat these diseases in vegetables, synthetic fungicides are used, but they are toxic and harmful to the environment. To address the rising global demand for food due to population growth, managing agriculture in a healthy, eco-friendly, and profitable manner is the prime target. Sustainable agriculture is most effective when combined with natural fungicides to reduce fungal infections in the agrarian ecosystem. Present study enlists the most common and effective natural plant based products which aimed to assess the antifungal efficacy of methanolic, ethanolic and aqueous extracts from three different medicinal plants, viz. Inula racemosa Hook. f, Salvia moorcroftiana Wall. Ex Benth and Euphorbia wallichii Hook f. these different plant extractswere screened for their antifungal activity against various phytopathogenic fungi, viz. Alternaria burnsii, Albifimbria viridis, Nigrospora sp., Mucor fragilis, Fusarium chlamydosporum, F. equiseti, F. solani, Curvularia lunata, Neocosmospora falciformis and Trichothecium roseum. The results in this study indicate that the combination of plant extracts has promising synergistic activity against plant pathogens, with concentration being a key factor in their effectiveness. These results provided useful information as a guideline for further evaluation of the effects of these extracts against plant diseases in greenhouse and field studies.